Transformation of Small-Scale Fishermen’s Economic Behavior towards Independent Entrepreneurship - Yoseb Boari; Tien Nova Bergita Yenusi (Universitas Prasetiya Mulya, 2025)
This study examines the process of transformation of small-scale fishermen's economic behavior from subsistence patterns to independent entrepreneurship. The study was conducted using a systematic literature review approach to 41 academic sources that include scientific articles, books, and policy documents that are relevant in the context of coastal development. The findings show that this transformation is influenced by a combination of structural, psychological, and social factors, including loss aversion, low access to capital and markets, and the strength of community social capital. In addition, the role of local institutions such as BUMDes and fishermen's cooperatives has proven crucial in shaping adaptive capacity and entrepreneurial mindsets. A community based development approach that integrates local wisdom, cultural values, and active community participation is the key to the success of the intervention. This study contributes to the literature by integrating behavioral economics and community-based development to propose a contextual model of fishermen’s behavioral transformation. The findings highlight the need for empowerment policies that are psychologically informed and locally grounded, particularly in small-scale coastal communities of Eastern Indonesia.